Presidential decree law no. 53/2014 amending some provisions of the income tax law no. 91/2005 and the stamp duty law no. 111/1980 - Egypt. Ministry of trade and industry. The Egyptian Customs Authority (2025)
Arab Republic of Egypt Presidential Decree-Law No. 53 of the year 2014 amending some provisions of the income tax law no. 91 of the year 2005 and the stamp duty law no. 111 of the year 1980